Optimalisasi Serifikasi Halal Sebagai Upaya Peningkatan Daya Saing Produk UMKM - Oktavia, Novi Nadila; Rahmawati, Yunita Rodho; Yunaini, Elsa Nenty; Janah, Miftachul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This study aims to examine the optimization of halal certification as a strategy to increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) products in Titik Village, Semen District. Halal certification is not only a necessity for Muslim consumers, but also a standard of quality and trust in products. The research method used is the PAR (Participatory Action Research) approach. The results of the study indicate that the low level of understanding of MSMEs regarding the procedures and benefits of halal certification is a major obstacle. In fact, the existence of halal certification can provide added value and expand the market, especially in the food and beverage sector. Therefore, synergy is needed between the local government, supporting institutions, and MSMEs in facilitating access to information and the halal certification process. By optimizing this certification, MSMEs in Titik Village have the potential to increase product competitiveness in both local and regional markets.